Esensialitas Tata Cara Pengelolaan Organisasi Sekolah dalam Menciptakan Sekolah Efektif: Studi Kasus MTS Annur Palangkaraya - Nandang Koswara; Rus'ansyah Rus'ansyah; Bidin Bidin; Akhmad Maki (LP. Ma'arif Janggan Magetan, 2023)
The school organization is an association under school management that aims to help create an effective condition for school activities. School management is related to the smooth functioning of the school as a whole. While school organization is about the organization of school resources, events, and personnel, organization in general is a systematic and effective association / relationship to achieve the desired results. This study aims to find out how the procedures for managing school organizations in order to create effective schools. In this study, researchers used a case study approach. Methods of data collection using observation, interviews, and documentation studies. The results of the study show that in carrying out school organizational management activities it involves an element of awareness of a sense of belonging so that the motivation to do school work is carried out optimally in accordance with mutually agreed terms. Through careful, systematic and diligent planning, as well as cooperation from various parties, a quality school organizational management system can be produced.